Transformasi Perilaku di Era Media Digital: Analisis Dampak Media Sosial terhadap Masyarakat - Najlaa Ayu Febrianti; Elsa Indah Sari; Tria Anugrah Lestari; Lisa Hoyalis; Panji Tri Utomo (Prosiding Seminar Nasional Ilmu Pendidikan, 2026)
The rapid growth of digital communication technologies has transformed social media into an integral part of everyday life, influencing how individuals communicate, interact, and perceive social realities. This study aims to analyze the impact of social media on behavioral transformation in the digital era, focusing on oversharing behavior, changes in communication ethics, social perception formation, shifts in social media usage patterns, and the self-diagnosis phenomenon among Generation Z. The research employed a qualitative approach using a library research method by examining relevant books, journal articles, research reports, and other academic sources. The findings indicate that social media significantly shapes social behavior by blurring the boundaries between private and public spaces, influencing communication ethics, affecting perceptions of social issues, increasing dependence on digital interaction, and contributing to self-diagnosis practices related to mental health. While social media provides broader access to information and social connectivity, it also presents challenges associated with privacy, misinformation, digital ethics, and psychological well-being. The study implies the importance of strengthening digital literacy, ethical communication practices, critical thinking skills, and awareness of privacy and mental health issues to support responsible social media use in contemporary society.